2020
DOI: 10.3390/molecules25143135
|View full text |Cite
|
Sign up to set email alerts
|

New Dihydroxytyrosyl Esters from Dicarboxylic Acids: Synthesis and Evaluation of the Antioxidant Activity In Vitro (ABTS) and in Cell-Cultures (DCF Assay)

Abstract: New dihydroxytyrosyl esters 2a, 2c–2j of dicarboxylic acids were synthesized from methyl orthoformate protected hydroxytyrosol 3 and diacyl chlorides. New compounds were characterized (HRMS, FT-IR, 1H- and 13C-NMR), and tested for antioxidant activity both in vitro (ABTS) and on L6 myoblasts and THP1 leukemic monocytes cell culture by DCF assay. According to the ABTS assay, compounds 2a, 2c–2j showed a TEAC value of antioxidant capacity up to twice that of Trolox. Very high or complete ROS protections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…44 In the study, the scavenging ability of TUR on ABTS•+ radicals and the protective effect on H 2 O 2 -induced PC12 cell oxidative damage were investigated to explore whether TUR had a similar or better antioxidant capacity and neuroprotective effects than those of CU. 45,46 The results revealed that TUR had a more substantial antioxidant capacity than CU or ascorbic acid. However, neither CU nor TUR significantly improved cell survival in a cell injury model.…”
Section: Discussionmentioning
confidence: 95%
“…44 In the study, the scavenging ability of TUR on ABTS•+ radicals and the protective effect on H 2 O 2 -induced PC12 cell oxidative damage were investigated to explore whether TUR had a similar or better antioxidant capacity and neuroprotective effects than those of CU. 45,46 The results revealed that TUR had a more substantial antioxidant capacity than CU or ascorbic acid. However, neither CU nor TUR significantly improved cell survival in a cell injury model.…”
Section: Discussionmentioning
confidence: 95%
“…Synthetic procedures have been also optimized to improve the bioavailability of HTyr and OLE. Lipophilic derivatives [ 57 , 58 , 59 , 60 , 61 ] and novel compounds were synthetized without modifying the catecholic moiety to be tested in vitro and in vivo as antioxidant, anticancer, anti-inflammatory, and neuroprotective agents [ 62 , 63 , 64 , 65 ]. Emerging research is devoted to developing drug delivery systems based on liposomes [ 66 ] and nanotechnology [ 67 ] for a better bioavailability and improved biological activities of both HTyr and OLE [ 68 ].…”
Section: Chemistry Of Hydroxytyrosol (Htyr) and Oleuropein (Ole)mentioning
confidence: 99%
“…A few works evaluated the overall flavonoid content by colorimetric assays in dried bulbs of Allium ursinum L. [ 113 ] and leaves of Rosmarinus officinalis L. [ 101 ] and Camellia sinensis L. [ 100 ]. The significative antioxidant power of polyphenols is strictly related to the presence of a catechol or pyrogallol moiety in the aromatic ring [ 203 , 207 , 208 , 209 ]. Iniguez-Franco et al reported a positive antioxidant performance from PLA functionalized with catechin or epicatechin by extrusion [ 107 ].…”
Section: Active Pla-based Materialsmentioning
confidence: 99%